Erythema infectious and its significance in pregnancy - analysis of knowledge among women - Socha, Agnieszka; Musz, Kinga; Dobko, Katarzyna; Frącz, Gabriela; Glac, Agata; Kuliga, Klaudia; Sejnowska, Natalia; Surowiec, Agata; Śnieżek, Kinga; Zając, Anna (Journal of Education, Health and Sport, 2023)
Introduced: Erythema infectious disease is a childhood infectious disease associated with a rash caused by parvovirus B19. The infection is especially dangerous for pregnant women. The disease can lead to intrauterine anemia and miscarriage, even when the pregnant woman did not have any clinical signs of infection. Aim of the study: The aim of the study was to assess the level of women's knowledge about erythema infectious and its importance in pregnancy. Materials and methods: The study conducted in May 2023 covered 150 women in various age groups. The research material was collected using an anonymous online questionnaire. The obtained results were analyzed and verified on the basis of scientific literature. Results: The percentage of respondents who had contact with erythema infectious is 64.7% and 64% correctly indicated parvovirus B19 as the etiological factor of the disease. 78% of respondents know that infection with erythema infectious is dangerous for pregnant women. 51.3% of respondents confirm that parvovirus B19 can cause fetal hydrops and 61.3% of women clearly indicate that even an asymptomatic course of infection in pregnant women can be a threat to the fetus. Conclusions: Women have basic knowledge about erythema infectious and its negative impact on pregnancy, but do not know details about complications and treatment. Women should be educated about the risk factors for the disease its symptoms and the effects of the disease. The aim is to minimize the risk of infection during pregnancy.